2000
DOI: 10.1007/bf03185660
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological combustion modeling of a direct injection diesel engine with in-cylinder flow effects

Abstract: A cycle simulation program is developed and its predictions are compared with the test bed measurements of a direct injection (01) diesel engine. It is based on the mass and energy conservation equations with phenomenological models for diesel combustion. Two modeling approaches for combustion have been tested; a multi-zone model by Hiroyasu et al (1976) and the other one coupled with an in-cylinder flow model. The results of the two combustion models are compared with the measured imep, pressure trace and NOx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…When the injection timing was set at 26° BTDC, the fuel was found to be sufficiently mixed with air before the ignition started, regardless of whether there was swirl or not. This finding was in good agreement with a previous computational study that indicated that the early injection timings led to longer ignition delays and promoted premixture formation . With regard to the swirl effect on combustion, the flame tended to be distributed around the cylinder wall without SCV (e.g., case a), whereas combustion occurred at the center of the chamber area with SCV (e.g., case b).…”
Section: Resultssupporting
confidence: 90%
“…When the injection timing was set at 26° BTDC, the fuel was found to be sufficiently mixed with air before the ignition started, regardless of whether there was swirl or not. This finding was in good agreement with a previous computational study that indicated that the early injection timings led to longer ignition delays and promoted premixture formation . With regard to the swirl effect on combustion, the flame tended to be distributed around the cylinder wall without SCV (e.g., case a), whereas combustion occurred at the center of the chamber area with SCV (e.g., case b).…”
Section: Resultssupporting
confidence: 90%
“…This is in agreement with what reported by Kibum [22] when analysing flame visualizations in a single-cylinder optical diesel engine; when the injection timing was set at 26°BTDC, the fuel was found to be sufficiently mixed with air before the ignition started, regardless of whether there was swirl or not. This was in good agreement also with a previous computational study that indicated that the early injection timings promoted premixture formation [23]. The pilot fuel distribution in Figure 9 indicates that some fuel is always exposed to the glow plug in the crucial period close to TDC and that the main injection is into an area where conditions are primed for combustion even if swirl ratio is decreased from 1.6 to 1.0.…”
Section: Figures 4 and 5 Provide Detailed Fuel Distribution Informatisupporting
confidence: 91%
“…This method gave good agreement with the experimental results carried out in two diesel engines, Isuzu and Caterpillar. Yong et al [6] developed results of a simulation computer program in a direct injection diesel engine and compare it with tests carried out on a test bench by testing of two modelling combustion approaches (multi-zone model and in-cylinder flow model). A thermodynamic simulation model studied in the paper of Salah et al [7], shows its ability to predict the impact of operating conditions on the combustion characteristics of a constant volume engine.…”
Section: Introductionmentioning
confidence: 99%